The role of substance use disorders in experiencing a repeat opioid overdose, and substance use treatment patterns among patients with a non-fatal opioid overdose. (1st April 2020) - Karmali, Ruchir N.; Ray, G. Thomas; Rubinstein, Andrea L.; Sterling, Stacy A.; Weisner, Constance M.; Campbell, Cynthia I.
Highlights: Patients with opioid use disorder had a higher 1-year risk of repeat overdose. Substance use service and buprenorphine use rates were low before the index overdose. Overdose was associated with higher substance use treatment rates post-overdose. After the index overdose, substance use treatment rates increased and then declined. Abstract: Background: A non-fatal opioid overdose (NFOO) increases the risk of another overdose and identifies high-risk patients. We estimated the risk of repeat opioid overdose for patients with and without substance use disorder (SUD) diagnoses and the change in substance use treatment utilization rates associated with the first NFOO. Methods: We selected patients (>18 years of age) from Kaiser Permanente Northern California with a NFOO between 2009-2016 (n = 3, 992). Cox proportional hazards models estimated the 1-year risk of opioid overdose associated with SUD diagnoses (opioid, alcohol, cannabis, amphetamine, sedative, and cocaine), controlling for patient characteristics. Among patients with an index NFOO, we calculated monthly utilization rates for outpatient substance use services and buprenorphine before and after the index overdose. Interrupted time series models estimated the change in level and trend in utilization rates associated with the index overdose. Results: Approximately 7.2 % of patients had a repeat opioid overdose during the year after the index NFOO. The only SUD diagnosis significantly associated with greater risk of repeat overdose was opioid use disorder (OUD) (aHR: 1.51; 95 % CI: 1.13–2.01). Before the index overdose, 4.16 % of patients received outpatient substance use services and 1.32 % received buprenorphine. The index overdose was associated with a 5.94 % (standard error: 0.77 %) absolute increase in outpatient substance use services and a 1.29 % (standard error: 0.15 %) increase in buprenorphine. Conclusion: Patients with a NFOO and OUD are vulnerable to another overdose. Low initiation rates for substance use treatment after a NFOO indicate a need to address patient, provider, and system barriers.